Rapid characterization of protein epitopes recognized by monoclonal antibodies using direct probing on thin-layer and paper chromatograms - Dowse, Carol; Carnegie, P.R.; Kemp, B.E.; Sheng, H.Z.; Grgacic, E.V.; Bernard, C.C.A. (Elsevier, 1987)
A simple method for the comparison and identification of protein epitopes recognized by monoclonal antibodies directly on thin-layer plates and 3MM paper chromatograms is described. Enzyme digests of myelin basic protein were separated on thin-layer plates and 3MM paper, fixed with glutaraldehyde and probed directly with affinity-purified mouse monoclonal antibodies. Detection of the immunoreactive peptides was enhanced using a second rabbit anti-mouse immunoglobulin and finally located using an alkaline phosphatase-conjugated anti-rabbit immunoglobulin. By probing the same enzyme digests of MBP with various monoclonal antibodies raised against MBP, a different binding 'pattern' of reactive peptides is rapidly obtained for monoclonal antibodies of differing specificities. This procedure was extended to the identification of the antigenic determinant using synthetic peptides. The major advantages of this procedure are its simplicity, non-radioactive nature and speed. Furthermore, there is the possibility of sequencing immunoreactive peptides eluted from the 3MM paper. © 1986.